A systematic review and thematic analysis of cinema in medical education. Issue 1 (25th January 2012) - Darbyshire, Daniel; Baker, Paul
Abstract : The use of cinema in medical education has the potential to teach students about a variety of subjects, for instance by illustrating a lecture on communication skills with a clip of Sir Lancelot Spratt ( Doctor In The House, 1954) demonstrating a paternalistic, doctor-centred approach to medicine or nurturing an ethical discussion around palliative care and dying using the cinematic adaptation of American playwright Margaret Edson's Wit (2001). Much has been written about this teaching method across several medical academic disciplines. It is the aim of this review to assimilate the various experiences in order to gain an insight into current expertise. The results are presented by the following headings under which the articles were examined: the source journal, year of publication, article type, theme, content, target, authors, if a clip or the entire film was used, and if any feedback was documented. This is followed by a chronological account of the development of the literature. Such an approach will allow the reader to gather specific information and contextualise it. This review does not critically appraise the quality of the evidence nor does it determine its validity, rather it is hoped that having read the review educators will know where to locate previous accounts of work that will help them develop more engaging pedagogy.